An insurgent path to democracy: popular mobilization, economic interests and regime transition in South Africa and El Salvador - Wood, Elisabeth Yean (2001)
In El Salvador and South Africa, mobilizatin by the economically and socially marginalized impelled the transition to democracy, forcing the initial liberalization of the regime and eventulally laying the political and economic foundations for democratizing compromise. These cases thus provide an opportunity to analyze one mechanism by which mobilization "from below" impels some regime transitions. In this insurgent path to democracy, sustained mobilization by poor and working class people transformed key interests of economic elities, leading to pressure on the state to compromise with the insurgents, thereby strengthening regime moderates over hard-liners with the result that negotiated transitions to democracy followed. The dramatis personae of these transitions were not contending elite factions, as in the most Latin American and southern European transitions, but representatives of distinct classes whose conflict of economic interest propelled the conflict and whose economic interdependence contributed to the structural basis of its democratizing resolution. - Reproduced.
Keywords: Politics and government - South Africa; Politics and government